Citation Analysis of Doctoral Theses in Civil Engineering Submitted to Visvesvaraya Technological University, Belagavi - H, Bhimappa S; Mulla, KR (Journal of Advanced Research in Library and Information Science, 2022)
The present study is based on 8208 citations, appended in the 42 Ph.D theses of Civil Engineering submitted to Visvesvaraya Technological University Belgravi  for the award of doctoral degree during the period 2007-2017. The main purpose of this study was to investigate authorship pattern of the citations, type and form of literature cited, and compiled a rank list of core journals in Civil Engineering. The study revealed that journals were the most preferred sources of information used by the researchers in the field of Civil Engineering accounting for 66.02% of total citations, followed by books with 12.58 % citations. The Applied Mechanics and Materials has ranked the first with 351 citations accounting for 8.32% of the total journal citations. Advanced Materials Research journal 6.54% occupies the second rank getting 276 citations, followed by Construction And Building Materials journal 3.70% with 156 citations. Authorship pattern for journal citations shows that most of the citations were contributed by multi authors. How to cite this article:  Bhimappa SH, Mulla KR. Citation Analysis of Ph.D Theses in Civil Engineering Submitted to Visvesvaraya Technological University, Belagavi. J Adv Res Lib Inform Sci 2022; 9(1): 11-18.